Role of HRCT for Rapid Triage of Patients with COVID-19 Pneumonia - Hina Hafeez Abbasi , Misbah Durrani , Umm e Kalsoom ,Anum Zahoor ,Fizza Batool , Shawana Sharif (Journal of Rawalpindi Medical College, 2021)
Background: To assess the diagnostic performances of HRCT for COVID 19 pneumonia for efficient triage of patients, in comparison with RT-PCR reverse transcription polymerase chain reaction test. Method: It is retrospective comparative study conducted in Benazir Bhutto hospital affiliated with Rawalpindi medical university from March 25th to April 25th, 2021. HRCT of 500 patients were selected from central computer server and their RT-PCR results were also obtained from the HMS system of the hospital. HRCT were reported as “Definitely COVID positive”, “Possible COVID positive” or “COVID negative” by experienced radiologists. Sensitivity, Specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated using the final RT-PCR test as standard of reference. Results: RT-PCR test of 207 patients was positive, whereas 293 were reported negative. HRCT was reported as “Definitely COVID positive” in 222 cases (44.4 %), “Possible COVID positive” in 24 cases (4.8%) and “COVID negative” in 254 cases (50.8%). Comparing only Definitely COVID positive category with RT-PCR results sensitivity, specificity. PPV and NPV were 90.3%, 88%,84.2% and 92.8% Conclusion: CT chest is the most reliable, sensitive and rapid tool for triaging of patients as COVID positive or negative in busy emergency departments as compared to RT-PCR which is time consuming and has limitations such as faulty sampling technique, limited kits and variable sensitivity